A novel characteristic index for frosting suppression based on the configuration and operation of air source heat pumps. (January 2020) - Liang, Shimin; Wang, Wei; Sun, Yuying; Li, Zhaoyang; Zhao, Jihan; Lin, Yao; Deng, Shiming
Highlights: A characteristic index of frosting suppression, CICO, for ASHPs was defined. CICO was based on the configuration and operation of ASHPs. An empirical numerical relationship for CICO was established. CICO can be used to evaluate the frosting suppression performances of ASHPs. Abstract: It has been known that for space heating ASHPs, their different configurations and operation may influence their frosting performances. However, there has been not a single index that can be used to comprehensively and realistically evaluate the frosting suppression performances for a space heating ASHP unit by considering all the influencing configurational and operational factors. Therefore, in this paper, a novel characteristic index for frosting suppression based on the configuration and operation of ASHPs has been proposed and its development is reported. Firstly, the characteristic index, CICO, was defined, a detailed analysis on the heat transfer taking place in the outdoor coil of an ASHP was carried out, and the relationship between CICO and temperature difference in the heat transfer between outdoor coil and ambient air (Δ T ) was established. Secondly, the description of an experimental setup with four experimental ASHP units is given. The set was used to establish all empirical numerical relationship between CICO and Δ T . Thirdly, using the experimental results, the empirical numerical relationship between CICO and Δ T was established, which suggested that a higher CICO would lead to a smaller Δ T, thus a better frosting suppression performance. The development results suggested that the index of CICO could be used to evaluate the level of frosting suppression performance for ASHPs, and to help improve the frosting suppression performances for an ASHP during its design and operation, to ensure its best possible operation performance.